Analysis of Motivation, Commitment and Workload of Officers on the Implementation of Early Detection of Hepatitis B in Pregnant Women in Sumenep District - Agusta Dian Ellina; Indah Winarni (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Hepatitis B virus is caused by exposure to virus-infected blood products, sexual activity or perinatal transmission. Transmission of hepatitis B virus from mother to baby can be prevented by screening/detecting hepatitis B virus in pregnant women and hepatitis B vaccination in infants. In general, this study was conducted to analyze the effect of motivation, commitment and workload of officers on the implementation of the hepatitis B early detection program in pregnant women in Sumenep District. This type of research is an observational study with a cross sectional design on 100 officers implementing early detection of hepatitis B in pregnant women in Sumenep District. Data collection instrument in the form of questionnaires and data analysis using ordinal logistic regression test. The results of the study of the motivation of most of the respondents were high (46%), commitment of most respondents is high (50%), the workload of most respondents is moderate (56%), implementation of early detection of hepatitis B in pregnant women most of the respondents are good (52%). While the results of statistical tests, motivation has a significant effect on the implementation of early detection of hepatitis B in pregnant women by 63.5% with a p value of 0.000 < (0.05). commitment does not effect the implementation of early detection of hepatitis B in pregnant women with a p value of 0.996 > (0.05 ). Workload has a significant effect on the implementation of early detection of hepatitis B in pregnant women by 24.4% with p value 0.000 < (0.05).